An Analysis of Word Formation of English Slang Used in Straight Outta Compton Movie - Muhammad Hafiza; Rusdi Noor Rosa (English Language and Literature, 2020)
AbstractThe aim of this study was to find out the tendency of slang words used in Straight Outta Compton movie and word formation processes of slang words. The type of this study was descriptive qualitative. This research used the theory of word formation processes by George Yule (2010). The researcher found 6 types of word formation in slang words in the Straight Outta Compton movie script namely coinage, blending, clipping, compounding, acronym, and multiple-process. The data of slang words collected from the movie script. This study found that the most dominant type of word formation was blending with the percentage of 29.24%. It was followed by coinage and clipping with a proportion of 26.16% and 24.65% respectively. Then, it was followed by compounding with a percentage of 13.84%. Acronym and multiple-process were the least dominant ones with a percentage of only 3.07%. Keywords: Language Style, Slang word, Word Formation